A novel polymeric fluorescence sensor based on acrylated citric acid for detection of melamine adulteration: Application in milk powder - KÖK YETİMOĞLU, ECE; KAHRAMAN, MEMET VEZİR; ÇUBUK, SONER (My University, 2022)
Melamine selective acrylate citric acid (ACA) based polymeric membrane sensor was prepared by radical polymerization method and the sensor was characterized. The sensor showed a selective fluorescent response to melamine (λex/λem=388/425 nm). The sensor response is linear in the concentration range of 3.96x10-9 to 7.93x10-8 mol L-1, the optimum pH value is 6.0 and response time is less than 1 minute. Limit of detection (LOD) and limit of quantification (LOQ) were calculated as 2.32 x 10-10 mol L-1 and as 7.74 x 10-10 mol L-1, respectively. The sensor showed great selectivity towards melamine in the presence of a large number of molecules and ions. The performance of sensor was also confirmed by determining of melamine in milk powder sample and the results were compared with HPLC results and acceptable results were obtained. As a conclusion, the results revealed that the proposed sensor is an interesting alternative for melamine determination. Keywords: Adulteration; Fluorimetric sensor; Melamine; Milk powder; Polymeric sensor.
Keywords: Kimya; Temel Bilimler; Chemistry; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; CHEMISTRY; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Kimya (çeşitli); Genel Kimya; Fizik Bilimleri; Multidisciplinary; Chemistry (miscellaneous); General Chemistry; Physical Sciences; Adulteration; Fluorimetric sensor; Melamine; Milk powder; Polymeric sensor; RESONANCE ENERGY-TRANSFER; GOLD NANOPARTICLES; CYANURIC ACID; NANOCLUSTERS; PRODUCTS; PROBE; Adulteration; Fluorimetric sensor; Melamine; Milk powder; Polymeric sensor